Surgical Capacity in Public and Private Health Facilities After a Five-Year Strategic Plan Implementation in Ethiopia: A Cross Sectional Study - Kassa Haile Merga; Senedu Bekele Gebreegziabher; Edlawit Mesfine Getachew; Manual Kassaye Sibhatu; Hassen Mohammed Beshir; Tsegaye Hailu Kumssa; Akililu Alemu Ashuro; Endawoke Amsalu Alemayue; Mikiyas Teferi; Desalegn Bekele Taye; Berhane Redae Meshesha; Wuletaw Chane Zewude; et al. (Ubiquity Press, 2023)
Background: Surgical capacity is critical for ensuring optimum access to safe, affordable, and timely emergency and essential surgical care (EESC) in low- and middle-income countries (LMICs) like Ethiopia. A five-year strategic plan has been implemented during 2016-2020 in Ethiopia to improve surgical capacity. Objectives: This study aims to evaluate the impact of the five-year strategy in surgical capacity in the country. Methods: A cross sectional survey was conducted in 172 health care facilities in Ethiopia from December 30, 2020, to June 10, 2021. Descriptive statistical analysis was done using STATA statistical software Version 15. Findings: A total of 2,312 surgical workforces were available and, the surgical workforce to population ratio ranged from 1.13:100,000 for public specialized hospitals to 10.8:100,000 for health centre operation room (OR) blocks. Surgical bed to population ratio was 0.03:1000 population, and the average numbers of OR tables per facility were 34. Nearly 25% and 10% of OR tables were not functional in public primary hospitals and private hospitals, respectively. The average surgical volume to population ratio was 189:100,000. Conclusions: Following the implementation of surgical care strategy, the surgical workforce density has increased. However, the study revealed that there is still a huge unmet gap in surgical capacity. The improvement in surgical volume is very low compared to the increment in the surgical workforce density. In addition to the investment being made to build surgical capacity, emphasis needs to be put on surgical system design and strengthening surgical system efficiency.